NMDAR-Mediated Calcium Transients Elicited by Glutamate Co-Release at Developing Inhibitory Synapses - Kalmbach, Abigail; Kullmann, Paul H.; Kandler, Karl (Frontiers in Synaptic Neuroscience, 2010)
Before hearing onset, the topographic organization of the inhibitory sound localization pathway from the medial nucleus of the trapezoid body (MNTB) to the lateral superior olive (LSO) is refined by means of synaptic silencing and strengthening. During this refinement period MNTB-LSO synapses not only release GABA and glycine but also release glutamate. This co-released glutamate can elicit postsynaptic currents that are predominantly mediated by NMDA receptors (NMDARs). To gain a better understanding of how glutamate contributes to synaptic signaling at developing MNTB-LSO inhibitory synapse, we investigated to what degree and under what conditions NMDARs contribute to postsynaptic calcium responses. Our results demonstrate that MNTB-LSO synapses can elicit compartmentalized calcium responses along aspiny LSO dendrites. These responses are significantly attenuated by the NMDARs antagonist APV. APV, however, has no effect on somatically recorded electrical postsynaptic responses, indicating little, if any, contribution of NMDARs to spike generation. Small NMDAR-mediated calcium responses were also observed under physiological levels of extracellular magnesium concentrations indicating that MNTB-LSO synapses activate magnesium sensitive NMDAR on immature LSO dendrites. In Fura-2 AM loaded neurons, blocking GABAA and glycine receptors decreased NMDAR contribution to somatic calcium responses suggesting that GABA and glycine, perhaps by shunting backpropagating action potentials, decrease the level of NMDAR activation under strong stimulus conditions.